Permanence and Global Attractivity of a Discrete Two-Prey One-Predator Model with Infinite Delay - Zhixiang Yu; Zhong Li (Discrete Dynamics in Nature and Society)
A discrete two-prey one-predator model with infinite delay is proposed. A set of sufficient conditions which guarantee the permanence of the system is obtained. By constructing a suitable Lyapunov functional, we also obtain sufficient conditions ensuring the global attractivity of the system. An example together with its numerical simulation shows the feasibility of the main results.